North American Youth Sport Institute
Technical Support, Consulting, Educational Training, Targeted Presentations, Writing and Editing, Publishing, and the sale of Educational Resources are provided for those served. Customers and clients are individuals (i.e., teachers, parents, coaches, community leaders, youth work professionals), groups, organizations, corporations, and businesses that direct their effort toward tots, children and teenagers in Fitness, Recreation, Education, Sport and Health (FRESH). The North American Youth Sport Institute (NAYSI) was founded by Jack Hutslar in 1979 and is now a division of Paradox Group Ltd.